Polarized and political : evaluating language per candidate hashtags of the 2016 American election - Collier, Margaret (2019)
By examining Twitter reactions to the 2016 election that both celebrate and condemn the results, this thesis aims to understand the online language patterns associated with a politically polarized culture, and to understand for what purpose social media users employ these language patterns. Two data sets of 100 tweets each were collected via two topical hashtags: 1. #makeamericagreatagain and 2. #imstillwithher. This thesis was guided through past scholarly research that examines trends in language usage on social media, dealing with topics such as authenticity and language policing. The two research questions that were established and then answered in this thesis were 1. What are the recurring commonalities in language usage by politically vocal users of social media, and what patterns do these commonalities create? and 2. What identities, social ideas, and relations are being expressed by the language patterns and trends? Three qualitative methods were used to provide thorough and unbiased answers to these questions.